Thiopeptide Engineering: A Multidisciplinary Effort towards Future Drugs. Issue 26 (23rd May 2014) - Just‐Baringo, Xavier; Albericio, Fernando; Álvarez, Mercedes
Abstract The recent development of thiopeptide analogues of antibiotics has allowed some of the limitations inherent to these naturally occurring substances to be overcome. Chemical synthesis, semisynthetic derivatization, and engineering of the biosynthetic pathway have independently led to complementary modifications of various thiopeptides. Some of the new substances have displayed improved profiles, not only as antibiotics, but also as antiplasmodial and anticancer drugs. The design of novel molecules based on the thiopeptide scaffold appears to be the only strategy to exploit the high potential they have shown in vitro. Herein we present the most relevant achievements in the production of thiopeptide analogues and also discuss the way the different approaches might be combined in a multidisciplinary strategy to produce more sophisticated structures.